Evaluate the definite integral from 2 to -2: Integral (x^2+3)^2 dx

### 1 Answer | Add Yours

`int_-2^2 (x^2 +3)^2 dx = int_-2^2 (x^4 + 6x^2 +9) dx`

`==> int_-2^2 (x^4 + 6x^2 + 9)dx = x^5/5 + 6x^3/3 + 9x`

`==> int_-2^2 (x^4 + 6x^2 + 9) dx = x^5/5 + 2x^3 + 9x`

`==> (-2^5)/5 + 2(-2^3) + 9(-2) = -32/5 + 2*(-8) - 18 = -32/5 -16 -18 = -40.4`

`==> (2^5)/5 + 2(2^3) + 9(2)= 32/5+16+18 = 40.04`

`==>40.4 - (-40.4)= 40.4 + 40.4 = 80.8`

`==> int_-2^2 (x^2+3)^2 dx = 80.8`

``

``

``

### Join to answer this question

Join a community of thousands of dedicated teachers and students.

Join eNotes